Pengaruh Rasio Keuangan terhadap Perubahan Harga Saham - Umi Murtini; Shinta Mareta (Fakultas Bisnis UKDW, 2006)
One factor that supports investors' trust on capital market istheir perception to the fiuingness of stock price. The more appropriate and quicker the information reflected by stock price delivered to investors, the more fficient the stock market. fhe information needed from the firm's financial statement if it's tooked from investor needs who would purchase a stock are stock price information, earning per sltare, total asset, earning after tax, net sale, total liabitity, and totat equity which is used to the company financing source. This research aims toexamine the effect of Price Earning Ratio (PER), Return on Assets (RoA), Net Profit Margin (NPM), Debt Equity Ratio (DER) changes to stock price changes either partially or simultaneously. This research proves that Price Earning ratio (PER) and Net Profit Margin (NpM) changes partially influence the change of stock price, whereas those four variables simultaneously influence the change of stock price. Thisresearch hopefully could give benefits to investors, emitens, and other partles as additional evaluating tools in the relation with the process of stock investment decision making when stock prices are fluctuative. This research is hopefully beneficial for emitens in making a wisdom relating to PER, RoA, NPM, and DER and can give additional lorcwledge and information for parties who need reference as well as literqture about financial management.Keywords: closing price, EAT, PER, DER, NPM, ROA